2011
DOI: 10.1097/tp.0b013e31821bf157
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Glomerulonephritis Under Rapid Discontinuation of Steroids

Abstract: Background Recurrent glomerulonephritis (GN) remains an important cause of kidney allograft loss and whether rapid discontinuation of steroids (RDS) is associated with a higher risk of recurrence is not known. Methods We studied recurrence rate, and graft and patient survival in four groups of recipients: 216 recipients with GN transplanted under RDS (group 1), 978 concurrent non-GN recipients transplanted under RDS (group 2), 260 historic comparator group transplanted for GN between 1994 and 1999 with stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
2
25
4
Order By: Relevance
“…Our finding of increased incidence of IgAN recurrence and shorter graft survival associated with sirolimus is interesting and contrary to that reported by Kukla et al., who observed a lower risk of recurrent glomerulonephritis with sirolimus . In contrast to the Kukla et al.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding of increased incidence of IgAN recurrence and shorter graft survival associated with sirolimus is interesting and contrary to that reported by Kukla et al., who observed a lower risk of recurrent glomerulonephritis with sirolimus . In contrast to the Kukla et al.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study by Kukla et al. has also shown a higher risk of recurrence of primary glomerulonephritis with steroid avoidance . In our study, patients withdrawn from steroids more than six months after transplantation appeared to have a similar low risk of IgAN recurrence as those maintained on steroids (by Kaplan–Meier analysis), possibly suggesting safety of steroid removal at this time point post‐transplant.…”
Section: Discussionsupporting
confidence: 78%
“…Recurrence of some glomerulopathies following steroid avoidance has been noted to be higher than with steroid continuation. Patient and graft survival was not affected in patients inducted on rATG and maintained on TAC and MMF [44,52]. In a study comprising 124 kidney transplant recipients, of whom 91% were on rATG induction Visger et al, also had the same results as shown by Kuklan [44,53].…”
Section: Steroid Minimization and High Immunological Risksupporting
confidence: 67%
“…It has been hypothesized that CS minimization may increase post-transplant glomerulonephritis recurrence. In a major retrospective study, it was found that recurrence rate was indeed higher with rapid CS discontinuation compared to CS maintenance for all glomerulonephritis types (hazard ratio 4.86, 95%CI: 2.34-10.07, P < 0.0001)[27]. The analysis also showed no difference in patient, allograft, and death-censored allograft survival.…”
Section: Discussionmentioning
confidence: 99%